Using Integrated Ecosystem Assessments to Build Resilient Ecosystems, Communities, and Economies. Issue 1 (2nd January 2021) - Spooner, Ellen; Karnauskas, Mandy; Harvey, Chris J.; Kelble, Chris; Rosellon-Druker, Judith; Kasperski, Stephen; Lucey, Sean M.; Andrews, Kelly S.; Gittings, Stephen R.; Moss, Jamal H.; Gove, Jamison M.; Samhouri, Jameal F.; et al.
Abstract: Science-based natural resource management is necessary for agencies to effectively meet their goals and mandates. However, this scientific basis needs to be advanced and evolved with ecosystems experiencing unprecedented events that challenge conventional management frameworks. Effectively managing marine resources and achieving agency missions requires more than meeting independent mandates and managing individual resources as chronic stressors overwhelm conventional management frameworks. Global science organizations are transitioning to interdisciplinary and holistic research to integrate human well-being as a key outcome. The United States' principal federal agency tasked with managing coastal and marine ecosystems is the National Oceanic and Atmospheric Administration (NOAA). NOAA's vision is "healthy ecosystems, communities and economies that are resilient in the face of change". NOAA adopted the Integrated Ecosystem Assessment (IEA) approach to conduct the collaborative science necessary for ecosystem-based management. IEAs have been employed for over a decade to develop science, tools, and collaborations that address complex ecosystem challenges and make progress toward NOAA's vision. This paper demonstrates, through case studies, how scientists, stakeholders, and managers build trust and meaningful relationships from the IEA approach. These case studies further demonstrate how the IEA approach can be adapted to various geographic and management scales to build trust with partners and provide the ecosystem science, including social science, required to build resilient coastal ecosystems, communities, and economies.